Reasons, Commitments, and Meanings: A Phenomenological Exploration of Grandparents’ Parenting of a Child with Autism Spectrum Disorder - Evan Jovianto Pratama; Chr. Argo Widiharto; Ismah (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study aimed to explore the reasons, commitment and meaning of grandparenting in families caring for grandchildren with ASD aged 2-6 years. This study used a qualitative, phenomenological approach. Data were collected through semi-structured interviews with seven primary caregivers of children with ASD. They were analysed using content analysis and therapeutic and occupational science frameworks to reveal patterns of caregiving, adaptation, and subjective meaning. This study resulted in three main themes being identified: 1) motivational reasons for becoming the primary caregiver, which included a sense of responsibility to the family and concern for the child’s safety and well-being; 2) the forms of caregiving work commitments undertaken by grandparents, including time management, adjustments to parenting strategies, and handling behaviours typical of ASD; and 3) the meaning of the emotional dimension of this role, which was characterised by long-term commitment, a sense of moral responsibility, and a deep bond of affection. Keywords: grandparenting, autism spectrum disorder, parenting, phenomenology